(untitled) (Andamios, Revista de Investigación Social, 2015)
In addition to a political regime, democracy is a cultural climate with social change. Intellectuals are challenged by this new and uncertain atmosphere. How do they experience the democratic pressures? The essay answers this question through the analysis of the intellectual’s democratic adaptation mechanism and effects.